ISOLATION AND CHARACTERIZATION OF PHYTASE PRODUCING BACTERIAL ISOLATES FROM SOIL - G. Aziz; M. Nawaz; A. A. Anjum; T. Yaqub; Mansur-ud-din Ahmed; J. Nazir; S. U. Khan; K. Aziz (Journal of Animal and Plant Sciences, 2015)
Phytase is an enzyme which breakdown the complex organic (unavailable) forms of phosphorous such as phytic acid into simpler inorganic (available) forms. Aim of the present study was to isolate, characterize and optimize physicochemical conditions of phytase producing bacteria. Phytase producing bacterial isolates were screened on phosphate solubilizing media. Isolates (PHY02, PHY03, PHY06, PHY07, PHY12, and PHY30) were identified by morphological, microscopic, and biochemical characteristics as Lactobacillus casei, Enterobacter intermedius, Bacillus badius, Escherichia coli, Shigella spp., and Klebsiella spp., respectively. All isolates (PHY02, PHY03, PHY06, PHY07, PHY12, and PHY30) produced optimum level of phytase on 37°C (27, 9, 19, 40, 19, and 32 IU/ml, respectively), pH 6.5 (26, 15, 19, 41, 19, and 32 IU/ml, respectively) and 1% NaCl (27, 15, 17, 41, 18, and 32 IU/ml, respectively).  PHY03, PHY06, PHY07 and PHY12 had significantly higher (P<0.05) enzyme production when glucose was used as sole source of corbon, while 0.3% lactose was preferred by PHY02 and PHY30. Peptone was preferred nitrogen sources for PHY02, PHY12, PHY07 and PHY30, while tryptone was preferred by PHY03 and PHY06, respectively. Phytase producing bacterial isolates may be further analyzed and developed as indigenous biofertilizers.
Keywords: Rhizosphere; Phytase; E. coli; Lactobacillus casei; Bacillus badius